POSSIBILITY TO APPLY LIPOSOMAL ALPHA-2B INTERFERON FOR THE PREVENTION OF FLU AND OTHER ACUTE RESPIRATORY INFECTIONS - M.K. Erofeeva; V.L. Maksakova; M.G. Pozdnyakova; I.L. Kolyvanova ("Paediatrician" Publishers LLC, 2007)
Within recent years, a special attention has been paid to the nonspecific prevention of the acute respiratory disease related to the increase of the activity of the natural mechanisms for antiviral protection. The application of the liposomal forms of the different medications contributes to the directed transportation of the biodegraded protein substances. A special interest is aroused by the opportunity to orally apply protein medications, as their injection forms quickly degrade in the stomach. New Russian liposomal recombinant alphac2b interferon has antiviral, immuno-modulating and interferonogenic activity. The work demonstrates experience of the oral application form of the liposomal medication of recombinant alphac2b interferon - reaferoncesclipint for the extra prevention of flu and other acute respiratory infections among children. The application of this medication to prevent flu and acute respiratory infections in the dose of 250,000 Ме twice a week for the 4 weeks' period proved to be efficient within the group of the preschool children (aged between 7-10 years old) and manifested itself in the reduction of the flu and acute respiratory infections recurrence. Key words: flu, prevention, efficiency index, interferon.